Comparison of inflammatory markers in COVID-19 patients- a study based on disease severity groups - Riaz, Zahra; Mahmood, Namra; Sattar, Arooj; Tariq, Hira; Babar, Kanwal; Ahmad, Muhammad (Journal of the Pakistan Medical Association, 2023)
Objective: To compare different inflammatory markers in various coronavirus disease 2019 severity groups. Method: The cross-sectional, retrospective, comparative study was conducted at the Central Park Teaching Hospital, Lahore, Pakistan, and comprised data from April to June 2021 of coronavirus disease 2019 inpatients. The data was divided into mild, moderate and severe/critical category using the World Health Organisation interim guidelines. Data was analysed using SPSS 22. Results: Of the 50 patients, 29(58%) were males and 21(42%) were females. The overall mean age was 54.12±21.23 years. The mean age was 62±17.1years in critical group compared to 50±19.7 years in mild and 52±15.9 years in moderate groups. There were 8(16%) patients in the mild group, 16(32%) moderate and 26(52%) in the critical severity group. Mortality was the outcome in 19(38%) cases, and 14(73.7%) of them were in the critical group (p=0.03). C reactive protein, interleukin-6, serum ferritin and D-dimer levels were significantly different among the groups (p<0.05). Conclusion: Older people were found to have experienced coronavirus disease 2019 in more severe forms. The inflammatory markers were significantly high in patients with severe disease and were associated with high mortality. Key Words: COVID-19, SARS CoV-2, SARS coronavirus, C-reactive protein, Ferritin, Interleukin-6, Acute-phase protein, Severity of illness.